Determinants of Health Seeking Culture among Women of Childbearing Age - F. E. Ojong; G. E. Odinka; J. O. Emeka; A. M. O. Agba; E. M. Iyang; Pius U. Angioha; Mary U. Ojong-Ejoh; Tabe E. Ojong (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
This study examines the determinants of health-seeking culture among women of reproductive age in the Calabar Metropolis, Nigeria. The determinants identified in this study were belief systems, level of education, cost of healthcare services, and Proximity. The researcher used the descriptive survey design to sample the opinion of representatives and get a detailed description of the health-seeking culture of women of childbearing age using quantitative and qualitative data. Six hundred (600) women of childbearing age were sampled from residents in the Calabar Metropolis. Both quantitative and qualitative data were retrieved using the research questionnaire and in-depth interview schedule. The retrieved quantitative data (586) were subjected to frequency and percentage counts, and simple linear regression at a significance level of 0.05. In contrast, the qualitative data were transcribed to supplement the quantitative responses. In addition, the transcribed qualitative data were analysed by the researcher into themes based on the research objectives. The findings indicate that: there is a significant relationship between belief system and health-seeking culture among women of childbearing age; there is a substantial relationship between the level of education and health-seeking culture of women of childbearing age; the cost of healthcare has a meaningful relationship with the health-seeking culture of women of childbearing age, and there is a significant relationship between Proximity to healthcare facilities and health-seeking culture of women of childbearing age. The study concludes that women's health-seeking behaviour is significantly retrained by beliefs, education levels, cost, and Proximity. Based on this finding, it is recommended that people's opinions be strongly considered and instilled in healthcare practice. Also, reproductive health awareness should be created using various social media platforms to address issues arising from self-medication